Introducing Reflective Teaching Practice in Remote School: Teacher-Student Interaction Patterns - Reni Marlina; Hadi Suwono; Chokchai Yuenyong; Ibrohim; Susriyati Mahanal; Hamdani (Postgraduate, University of Mataram, 2023)
This study aimed to analyze classroom interactions in the reflective teaching practice based on learning objectives and types of interactions, types of student questions and answers, and gender and student achievement. Teacher-student interactions, particularly in reflective learning, have been discussed in depth in urban schools. However, few studies reported the interactions between teachers and students in remote areas. The data collected for this cross-sectional study are part of a broader longitudinal research project. The participants comprised 46 students and 4 teachers from 3 remote schools representing 3 districts in Indonesia. The results showed that most of the teacher-student interactions in reflective teaching practice contained feedback that focused on students' correct and incorrect answers yet rarely discussed how students got answers. Teacher reflection was evaluative by discussing matters related to learning objectives. While reflections have not yet been related to the teacher’s method. This study also reported that gender and achievement did not affect the reflective teaching practice.